Guillain-Barre syndrome: current understanding of the pathology (review) - Davydova, A. H.; Kurochkin, M. Yu.; Herasimchuk, T. S.; Kapustin, S. A.; Давидова, Анна Григорівна; Курочкін, Михайло Юрійович; Герасімчук, Тетяна Сергіївна; Капустін, Сергій Анатолійович (My University, 2023)
Guillain-Barré syndrome (GBS), also called acute inflammatory demyelinating polyneuropathy, is an acquired immune-mediated neuropathy, the development of which occurs due to an immune reaction to a previous immune-activating event (viral or bacterial infection, surgical intervention, etc.). It is the most common cause of acute neuromuscular weakness and paralysis worldwide.